Pengembangan media pembelajaran berbicara bahasa Prancis berbasis video pada siswa kelas XI SMAN 14 Jakarta - Tasya Ayu Safira; Wahyu Tri Widyastuti; Dian Savitri (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2023)
The purpose of this research is to develop French learning video media on speaking skills for grade XI. This research uses the research and development (R&D) method with the ADDIE model (Mulyatiningsih, 2016) which consists of 5 stages, this research only carried out 3 stages, namely analysis, design and development. This is due to the limited time available in the research. The learning video media was made based on the results of the needs questionnaire of students of class XI IPS 1 at SMAN 14 Jakarta, the results of interviews with French teachers and the results of classroom observations. This research produces French learning videos for class XI high school that can be accessed easily through the youtube channel. In the process of making the video, the researcher used VN and Canva Pro applications. This learning video consists of 2 videos where in video 1 using inviter quelqu'un, accepter et refuser l'invitation material lasts 8 minutes and in video 2 with féliciter quelqu'un material lasts 5 minutes. In each video there are illustrations and also some small exercises to train students' speaking skills. In addition, in the description column there is an exercise link that is directly connected to learningapps. This learning video has been validated by material experts and media experts with very feasible results with a note of making some improvements and adding some components to the video. After making improvements and additions according to the experts suggestions, this learning video media is ready to be tested in the field.